The role of plasma treatments of Cu interconnects in back-end-of-line reliability - Tan, Kwan Ling. (2010)
Reliability in BEOL interconnects is crucial. The time-dependent dielectric breakdown (TDDB) and electromigration strongly affect the reliability of Cu interconnects. Both rely on the surface condition of Cu with the Cu cap. Therefore, plasma treatment is carried out to improve adhesion between Cu and Cu cap layer. Previously, NH3 treatment is used but with serious growth of Cu hillocks. It is then changed to H2 treatment with significant reduction in Cu hillocks but accompanied by an increase in resistance and signs of grain boundary grooving. Therefore, the objective of the project is to understand the mechanism of grain boundary grooving caused by the H2 treatment. Different types of plasma treatments were carried out and the splits were characterized by techniques such as AFM, XRD, SEM and TEM to obtain surface morphology and stress data. It was found that resistance worsens with the increase in Cu hillocks, while the grain boundary grooving improves. However, a correlation with the stress condition cannot be made as XRD found no strain present in the splits. This may be due to the limitation of the resolution of XRD or its inability to detect the signal if the strain is nonhomogenous. TEM is still underway in the aim to find out the mechanism behind the dislocation nucleation sites. Therefore, there is a need to find a method to characterize the strain/stress present.